Mechanism of apoptosis inhibition to squamous cell carcinoma of oral cancer in cisplatin treatment - Wibowo, R Marjono Dwi; Perdanakusuma, David S; Tanggo, Eddy Herman (Folia Medica Indonesiana, 2017)
This study was to approve the increased secretion of Hsp 70, DNA damage, and inhibitor apoptosis protein in cisplatin therapy which influence apoptosis of oral cancer cell and to know mechanism of molecular pathology. This study was an in vitro experimental laboratory using Randomized Block Design. Cell culture of oral cancer divided from cisplatin resistance cancer cell and cancer cell never induce cisplatin. Two group of cancer cell would be given cisplatin therapy. Secretion of Hsp 70, DNA damage, Inhibitor of apoptosis protein, and apoptosis index would be examined. Cisplatin resistance cancer cell group showed lower apoptosis than never induce cisplatin cancer cell. Elevated secretion of Hsp 70 in cisplatin therapy group (p= 0.000, b=0.881). Lower secretion of DNA damage protein in cisplatin resistance cancer cell and it was not going apoptosis. In path regression analysis, cisplatin was significans through IAP pathway (p=0.000, b=0.726) to apoptosis. All type of cell cultures were also significans through IAP pathway (p=0.000, b=0.496) to apoptosis. Elevated IAP secretion influenced apoptosis (b= 1.000). In conclusion, cisplatin used IAP pathway to apoptosis. All type of cell cultures also used IAP pathway to apoptosis. Cisplatin resistance cell culture had stronger effect to IAP and IAP increased inhibition to apoptosis.